Lipid Profile Distribution and Dyslipidemia in Cardiac Patients: A Study at National Institute of Cardiovascular Diseases, Dhaka, Bangladesh - Amin, Md Nurul; Faruque, Ghulam Mohammed; Islam, Shitil Ibna (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Dyslipidemia, marked by abnormal lipid levels, is a significant risk factor for cardiovascular diseases (CVD), a leading cause of global morbidity and mortality. In Bangladesh, changing lifestyles and dietary habits have increased overweight and obesity rates, making it crucial to examine lipid profiles in cardiac patients. However, research on lipid profile distributions among ischemic heart disease patients at institutions like the National Institute of Cardiovascular Diseases (NICVD) in Dhaka is limited. This study aims to analyze lipid profile distributions in cardiac patients at NICVD, focusing on age and gender variations. Methods: This cross-sectional study involved 924 patients presenting with cardiac symptoms at NICVD between 2000 and 2009. Participants' lipid profiles were assessed using enzymatic colorimetric methods to measure total cholesterol (TC), triglycerides (Tg), high-density lipoprotein (HDL), and low-density lipoprotein (LDL). Dyslipidemia was defined using criteria proposed in the Textbook of Nutrition, “Contemporary Nutrition”. Accordingly, dyslipidemia was identified when the TC:HDL ratio was > 4.5 or when the Tg:HDL ratio was > 3.5. The types of dyslipidemia were classified as serum total cholesterol (TC) ≥ 200 mg/dL (hypercholesterolemia), triglycerides (TG) ≥ 150 mg/dL (hypertriglyceridemia), low-density lipoprotein (LDL) cholesterol ≥ 130 mg/dL (elevated LDL) and high-density lipoprotein (HDL) cholesterol < 40 mg/dL for men and < 50 mg/dl for women (Low HDL). Results: The study sample had a mean age of 49.6 ± 11.9 years, predominantly male (70%). Significant findings included that 37.4% of patients presented with hypercholesterolemia, 62.4% showed hypertriglyceridemia, and an alarming 82.9% had low HDL levels. Moreover, when assessing dyslipidemia through TC:HDL and TG:HDL ratios, nearly 90% of patients were identified as dyslipidemic. Age-related analysis indicated notable reductions in lipid parameters among older patients, except for triglycerides. Furthermore, gender disparities emerged, with elevated TC and LDL levels being more prevalent among females compared to males, with a strikingly 20-fold higher risk of low HDL observed in females compared to males (p < 0.001). Conclusions: The high prevalence of dyslipidemia among cardiac patients at NICVD emphasizes the urgent need for targeted public health strategies in Bangladesh. This study provides critical insights into age and gender disparities in lipid profiles, highlighting the necessity for tailored health education and management interventions to mitigate cardiovascular risks in the population. Ibrahim Card Med J 2024; 14(1): 12-18